Downward nominal wage rigidity in the OECD - Steinar Holden; Fredrik Wulfsberg (European Central Bank (ECB), 2007)
Recent micro studies have documented extensive downward nominal wage rigidity (DNWR) for job stayers in many OECD countries, but the effect on aggregate variables remains disputed. Using data for hourly nominal wages, we explore the existence of DNWR on wages at the industry level in 19 OECD countries, over the period 1973–1999. Based on a novel method, we reject the hypothesis of no DNWR. The fraction of wage cuts prevented due to DNWR has fallen over time, from 61 percent in the 1970s to 16 percent in the late 1990s, but the number of industries affected by DNWR has increased. DNWR is more prevalent when unemployment is low, union density is high, and employment protection legislation is strict.
Keywords: E3; J3; J5; 330; Downward nominal wage rigidity; employment protection legislation; oecd; Wage setting; Lohnrigidität; Arbeitsmarktflexibilität; Schätzung; OECD-Staaten